PENGARUH PROFITABILITAS, LIKUIDITAS, UKURAN PERUSAHAAN, DAN LEVERAGE TERHADAP NILAI PERUSAHAAN - Johanes, Joan; Jonnardi, Jonnardi (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
This study was conducted to empirically examine the effect of profitability, liquidity, firm size, and leverage on firm value. The sample selected through the simple random sampling method for this study were 35 consumer goods industrial sector companies listed on the Indonesia Stock Exchange (IDX) in the 2016-2020 period. The data used in this study is secondary data obtained from idx.co.id and related company websites. The data were processed using Microsoft Excel 2019 and Econometric Views (EViews) version 12.0 program. The results of this study indicate that profitability and leverage have a significant positive effect on firm value, while liquidity has an insignificant positive effect on firm value, and firm size has a significant negative effect on firm value.